The Formation of Modern Syria and Iraq - Ṭauber, Eliezer (Portland Frank Cass, 1995)
This volume examines the impact of clandestine and overt political organizations in Syria, Lebanon, Palestine and Iraq after World War I.
Include Notes, Bibliography and Index
Keywords: Middle East -- History -- 1914-1923 -- Iraq -- History -- 1534-1921 -- Syria -- History -- 20th Century